Determinants of Hypertension Occurrence in Women of Reproductive Age (15-49 Years) in the Working Area of the Sungai Tering Community Health Center, East Tanjung Jabung Regency in 2022 - Jessica Veronica Silalahi; Rd. Halim; Hendra Dhermawan Sitanggang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The incidence of hypertension is increasing in the world. Many factors cause hypertension both socio-demographic factors, behavior, physical and history of the disease. The purpose of this study was to analyze the determinants of the incidence of hypertension in women of childbearing age (15-49 years) in the Working Area of the Sungai Tering Public Health Center, East Tanjung Jabung Regency in 2022. This study used a cross sectional design. The research variables were age, family history, obesity, physical activity, seafood consumption, and hormonal contraception. Data collection used a questionnaire by conducting interviews, measuring blood pressure, measuring body weight and height. Sampling used Stratified random sampling, 120 samples of women of childbearing age were analyzed using the Cox-Regression test. The proportion of hypertension in the Sungai Tering Health Center working area is 43.35%. Factors associated with the incidence of hypertension in women of childbearing age are family history, physical activity, and consumption of seafood. Factors that are not related are age, obesity, and hormonal contraception. Healthy lifestyle behaviors such as a balanced diet, diligent physical activity, and regular health checks reduce the risk of developing hypertension.